Comparison of wound healing time post odontectomy surgery using silk and catgut sutures In Pirngadi Hospital - Rahmi Syaflida; Hendry Rusdy; Ahyar Riza; Marshall Sitorus (DiscoverSys Inc., 2019)
Objective: To compare post-odontectomy wound healing time using silk and catgut sutures at Pirngadi Hospital from May to June 2018.Material and Methods: This is anon-laboratory experimental study with a â€œpost-test onlyâ€design. Wound healing scores was assessed on the first and seventh days post odotectomy by seeing signs of inflammation. The number of patients studied was 30 people which 15 people used silk and 15 people used catgut.Results: The results were statistically analyzed using Mann-Whitney Test. There was no significant relationship (p> 0.05) between the wound healing time to the suture type on the first day post odontectomy. On the seventh day, it was found that there was a significant relationship (p <0.05) which silk had a score of 1.40 Â± 0.507 while catgut had a score of 1.07 Â± 0.258.Conclusion: Catgut has a better wound healing time than silk.